Interdependensi Variabel Makro Ekonomi terhadap Perkembangan Aset Perbankan Syariah - Noni Rozaini; M. Yusuf Harahap; M. Nasir Nasution (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This article aims to analyse the macroeconomic interdependence and development of sharia banking assets in Indonesia. This study employed quantitative method by using Vector Auto Regression (VAR) technique. The results of this study indicate that (1) Gross Profit Share Instrument based on Vector Error Correction Model (VECM) estimation result has significant influence with high coefficient of sharia banking ASET. (2) Profit sharing instruments based on the Impulse Response Function (IRF) analysis or dynamic behaviour of the model turns out to be the highest and highest variable responded by the research variables. (3) Sharing Instrument based on analysis of Variance Decomposition (VD) is a variable that has a composition and a large role responded by other variables. (4) ASSET instrument of sharia banking based on Impulse Response Function (IRF) and Variance Decomposition (VD) analysis.